Assessing the effectiveness of a community intervention for monkeypox prevention in the Congo basin. - Amira A Roess; Benjamin P Monroe; Eric A Kinzoni; Seamus Gallagher; Saturnin R Ibata; Nkenda Badinga; Trolienne M Molouania; Fredy S Mabola; Jean V Mombouli; Darin S Carroll; Adam MacNeil; Noelle A Benzekri; et al. (Public Library of Science (PLoS), 2011)
BACKGROUND: In areas where health resources are limited, community participation in the recognition and reporting of disease hazards is critical for the identification of outbreaks. This is particularly true for zoonotic diseases such as monkeypox that principally affect people living in remote areas with few health services. Here we report the findings of an evaluation measuring the effectiveness of a film-based community outreach program designed to improve the understanding of monkeypox symptoms, transmission and prevention, by residents of the Republic of the Congo (ROC) who are at risk for disease acquisition. METHODOLOGY/PRINCIPAL FINDINGS: During 90 days, monkeypox outreach was conducted for ∼23,860 people in northern ROC. Two hundred seventy-one attendees (selected via a structured sample) were interviewed before and after participating in a small-group outreach session. The proportion of interviewees demonstrating monkeypox-specific knowledge before and after was compared. Significant gains were measured in areas of disease recognition, transmission, and mitigation of risk. The ability to recognize at least one disease symptom and a willingness to take a family member with monkeypox to the hospital increased from 49 and 45% to 95 and 87%, respectively (p<0.001, both). Willingness to deter behaviors associated with zoonotic risk, such as eating the carcass of a primate found dead in the forest, remained fundamentally unchanged however, suggesting additional messaging may be needed. CONCLUSIONS/SIGNIFICANCE: These results suggest that our current program of film-based educational activities is effective in improving disease-specific knowledge and may encourage individuals to seek out the advice of health workers when monkeypox is suspected.